2002
DOI: 10.1007/s00125-002-0843-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces human TGF-β1 promoter activation: similarity to hyperglycaemia

Abstract: Aims/hypothesis. Activation of the renal renin-angiotensin system has been implicated in the pathogenesis of diabetic nephropathy. Because previous in vitro studies demonstrated the angiotensin II (ang II)-mediated up-regulation of the prosclerotic transforming growth factor β1 (TGF) we studied the molecular mechanism of ang II-induced TGF-β1 gene activation. Methods. Mesangial cells were stimulated with 100 nmol/l ang II with or without inhibitors of protein kinase C (PKC) and p38 MAPK and the TGF-β1 promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 39 publications
1
66
0
2
Order By: Relevance
“…However, mesangial cell hypertrophy induced by endothelin-1 is independent of p38 MAPK signalling [32]. High glucose and angiotensin II also promote TGF-β1 gene activation in mesangial cells by p38 MAPK signalling [33]. This in turn contributes to fibrosis [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, mesangial cell hypertrophy induced by endothelin-1 is independent of p38 MAPK signalling [32]. High glucose and angiotensin II also promote TGF-β1 gene activation in mesangial cells by p38 MAPK signalling [33]. This in turn contributes to fibrosis [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II acts through two receptors -AT1 and AT2, with AT1 activation playing a major role in the production of ECM proteins and vascular fibrosis 2,[95][96][97][98] . Whilst the precise mechanisms involved in angiotensin II related vascular fibrosis remain to be fully defined, increased activity of TGF-β-1, galectin-3, p38 MAPK and MMPs/TIMPs may all contribute.…”
Section: Angiotensin II Aldosterone and Endothelin-1mentioning
confidence: 99%
“…The mesangial ECM is the main cause of declining renal function in DN provides structural support for the glomerular capillary convolute, connecting with the extraglomerular mesangium at the vascular pole and dysregulation of cell-matrix signaling plays an important role in DN [2]. It was found that hyperglycemia induced TGF-expression in experimental and human diabetes [20,21]. Previous findings have demonstrated that high glucose stimulates TGF-β1 very early through its receptor [22,23].…”
Section: Discussionmentioning
confidence: 99%